Advanced zinc-doped adhesives for high performance at the resin-carious dentin interface. (September 2016) - Toledano, Manuel; Osorio, Raquel; Osorio, Estrella; García-Godoy, Franklin; Toledano-Osorio, Manuel; Aguilera, Fátima S.
Abstract: The purpose of this study was to evaluate the remineralization ability of an etch-and-rinse Zn-doped resin applied on caries-affected dentin (CAD). CAD surfaces were subjected to: (i) 37% phosphoric acid (PA) or (ii) 0.5 M ethylenediaminetetraacetic acid (EDTA). 10 wt% ZnO nanoparticles or 2 wt% ZnCl2 were added into the adhesive Single Bond (SB), to create the following groups: PA+SB, PA+SB-ZnO, PA+SB-ZnCl2, EDTA+SB, EDTA+SB-ZnO, EDTA+SB-ZnCl2 . Bonded interfaces were submitted to mechanical loading or stored during 24 h. Remineralization of the bonded interfaces was studied by AFM nano-indentation (hardness and Young׳s modulus), Raman spectroscopy [mapping with principal component analysis (PCA), and hierarchical cluster analysis (HCA)] and Masson׳s trichrome staining technique. Dentin samples treated with PA+SB-ZnO attained the highest values of nano-mechanical properties. Load cycling increased both mineralization and crystallographic maturity at the interface; this effect was specially noticed when using ZnCl2 -doped resin in EDTA-treated carious dentin. Crosslinking attained higher frequencies indicating better conformation and organization of collagen in specimens treated with PA+SB-ZnO, after load cycling. Trichrome staining technique depicted a deeper demineralized dentin fringe that became reduced after loading, and it was not observable in EDTA+SB groups. Multivariate analysis confirmed de homogenizing effect of load cycling in the percentage of variances, traces of centroids and distribution of clusters, especially in specimens treated with EDTA+SB-ZnCl2 . Graphical abstract: Highlights: EDTA-treatment of dentin facilitates functional remineralization after load cycling. ZnO application after phosphoric acid etching lead to mineral precipitation on dentin. ZnCl2 promoted formation of amorphous and crystalline minerals after load cycling. EDTA and ZnCl2 decreased carbonate substitution in carious dentin after load cycling.